Surgical management of adult supraclavicular hemangioma: a case report - Novita Sahniar S; Ivan Joalsen MT (Indonesian Vascular Access Association (IVAA), 2023)
Introduction: Hemangioma is one of the most common vascular anomalies. It is classified into two types: superficial hemangioma, also known as capillary hemangioma, which appears as brilliant red macular masses, and deep hemangioma, which appears as a soft, non-fluctuating, poorly defined, and occasionally bosselated nodule. Surgical excision is recommended for cavernous-type tumors, which are less sure to regress. Despite its benign origin and behavior, it can develop in any body part. However, its size and origin site may vary and make surgical excision more challenging due to the importance of the structures surrounding the mass. Thus, this study aims to explain the surgical management of adult supraclavicular hemangioma. Case Description: We present a case of primary cavernous hemangioma in 36 years-old-woman with no history of health problems that extends to the supraclavicular area and was linked to essential structures. The surgical excision was performed through a double-incision technique to prevent iatrogenic damage to the system. Postoperative evaluations revealed no impairment of motoric and sensory hand functions, and the patient was discharged three days postoperatively. Histopathologic findings were consistent with the diagnosis of hemangioma. Conclusion: The supraclavicular approach in surgery is challenging due to its critical location and closeness to key neurovascular structures. To obtain the best surgical outcome, the essential operating concepts include thorough dissection and a modified method to limit the risk of functional status and mobility impairment.